Costo de producción de la Hacienda Arrocera De Ángel Calero en el cantón Babahoyo en el periodo 2023. - Calero Álava, Janaly Lizbeth (2024)
The rice company of Ángel Calero is an industry that produces and markets grains, especially rice. This cereal is the basis of food for communities at the cantonal level and offers job opportunities to operators in the agricultural area. For many years the company has been dedicated to the mass production of this cereal, taking as a reference projections in costs and expenses incurred during the production process, which has generated significant variations. This project focused on identifying the factors that affect the profitability of the company, while at the same time knowing and breaking down the quantitative information provided by the institution to have a clear idea of the cost accounting of the business. Important details were noted that indicate that the aforementioned industry, by not having a detailed record of the costs incurred in the production process, makes it difficult to make correct decisions, and in turn there is a lack of financial education and ignorance in the accounting area on the part of those in charge. This study showed that the Calero rice industry produces this cereal in large volumes, making its profit margin recognizable in brief, but on the other hand, it is difficult to identify inefficiencies in the rice production process, because it is possible that nullities occur during the production process and there may be a loss of money or misuse of other resources that ultimately result in losses. By the way, this business has remained financially healthy over the years, since it has not presented significant decreases in its income.